Fusobacterium nucleatum promotes colorectal cancer liver metastasis via miR-5692a/IL-8 axis by inducing epithelial-mesenchymal transition - Yulong Yu; Han Yin; Bili Wu; Weiheng Zhao; Yuan Wang; Aifeina Aili; Mu Yang; Qianqian Yu; Xianglin Yuan (Journal of Biomedical Science)
Abstract Background The association between the intestinal microbiota and colorectal cancer (CRC) has been extensively studied, with Fusobacterium nucleatum (F. nucleatum, FN) being found in high abundance in colorectal cancer tissues. Previous research has emphasized the significant role of F. nucleatum in the occurrence of CRC. However, the impact of F. nucleatum on CRC liver metastasis has not been well understood. Methods The effects of F. nucleatum on metastasis ability of CRC cell were evaluated in vitro were examined by wound-healing assay and transwell assay. The mouse model of CRC liver metastasis was constructed by spleen injection, and the degree of liver metastasis was assessed by in vivo bioluminescence imaging. The gene expression changes in CRC cells after co-culture with F. nucleatum was analyzed through transcriptome sequencing. qRT-PCR and Western Blot assays were performed to validate the expression of related genes and proteins. Results The metastasis ability of CRC cells was significantly enhanced after co-culture with F. nucleatum in vitro. In the mouse model, F. nucleatum also promoted the development of liver metastasis in CRC. Mechanistically, F. nucleatum infection increased the expression of IL-8 by downregulated the level of miR-5692a, a regulatory microRNA of IL-8. This led to the activation of the ERK pathway and resulted in the epithelial-mesenchymal transition (EMT) of CRC cells. Conclusions Our results suggest that F. nucleatum promotes CRC liver metastasis by inducing epithelial-mesenchymal transition through the miR-5692a/IL-8 axis. These findings provide new insights for the prevention and treatment of colorectal cancer liver metastasis.